An Investigation into the Usage of ChatGPT in Academic Writing by EFL University Students in North and East Syria: A Cross-Sectional Study - Noman Ali Othman (TESOL Today, 2025)
This study investigates the role of ChatGPT in enhancing academic writing skills among EFL university students in North and East Syria (NES). With limited access to resources and timely feedback in traditional educational settings, EFL students frequently encounter difficulties in developing effective writing proficiency. Through a quantitative approach involving 350 third- and fourth-year students from Rojava University, this research reports students’ perceptions of ChatGPT, the perceived advantages, and the linguistics and pedagogical challenges of using ChatGPT. The findings reveal that students perceive ChatGPT as a highly supportive tool in various aspects of writing, including idea generation, grammar correction, vocabulary enrichment, and overall clarity. Despite these positive perceptions, concerns were noted regarding the tool’s potential to affect students’ originality, writing style, and ability to evaluate AI-generated content critically. The study concludes with recommendations for educators to integrate ChatGPT in academic writing instruction while encouraging reflection and critical engagement. Limitations and future research directions are discussed in the article.